2015
DOI: 10.5055/jom.2015.0270
|View full text |Cite
|
Sign up to set email alerts
|

Does tapentadol affect sex hormone concentrations differently from morphine and oxycodone? An initial assessment and possible implications for opioid-induced androgen deficiency

Abstract: These results suggest that tapentadol, which has combined MOR and NRI activities, may have a lower impact on sex hormone concentrations than pure opioid analgesics, such as morphine or oxycodone. The data and mechanistic rationale presented herein provide a justification for conducting additional hypothesis testing studies, and are not intended to be used as a basis for clinical decision making. Future studies may help elucidate whether the observed trends are clinically significant and would translate into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
4
14
0
2
Order By: Relevance
“…Surprisingly, despite the enhanced sexual activity observed in rabbits administered with codeine, serum levels of testosterone were lower in them. Although no study has documented the effects of codeine or any opioid on sexual performance, findings from this study corroborate those that reported the anti-androgenic activity of opioids (Eichenbaum et al, 2015;Daniell, 2016;Rubinstein & Carpenter, 2017;Lehtihet et al, 2018). Studies have reported a decline in serum levels of testosterone in tramadoltreated rats via oxidative stress-mediated testicular damage (Nna & Osim, 2017;Nna et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, despite the enhanced sexual activity observed in rabbits administered with codeine, serum levels of testosterone were lower in them. Although no study has documented the effects of codeine or any opioid on sexual performance, findings from this study corroborate those that reported the anti-androgenic activity of opioids (Eichenbaum et al, 2015;Daniell, 2016;Rubinstein & Carpenter, 2017;Lehtihet et al, 2018). Studies have reported a decline in serum levels of testosterone in tramadoltreated rats via oxidative stress-mediated testicular damage (Nna & Osim, 2017;Nna et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in testicular weight following codeine use explains the associated reduction of testosterone bioavailability and disrupted spermatogenesis observed in this study. The decline in the circulatory concentrations of testosterone seen in codeine treatment aligns with previous reports [15][16][17][18]. The decline in serum and testicular levels of androgen and cessation of spermatogenesis observed in codeine-treated animals could be partly due to codeine-induced loss of testicular tissues, and impairment of testicular metabolism and function.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, some of the nonopioid actions of the opioids could have affected testosterone levels. For example, opioids whose mechanism of action involves inhibition of norepinephrine reuptake may have a lower impact on testosterone levels than opioids whose analgesic effect is only through activation of opioid receptors [26]. Another shortcoming is that the daily dose of opioids taken by the participants was not known, so the effect of opioid dose was not assessed.…”
Section: Discussionmentioning
confidence: 99%